Odpowiedź :
Szczegółowe wyjaśnienie:
a) tak to chyba miało wyglądać
[tex](1 \frac{3}{4} ) ^{6} \times ( \frac{2}{7} ) ^{6} = ( \frac{7}{4} \times \frac{2}{7}) ^{6} = ( \frac{1}{2} )^{6} = \frac{1}{64} [/tex]
b)
[tex](0.8) ^{4} \div (2 \frac{2}{3} )^{4} = ( \frac{8}{10} \div \frac{8}{3} )^{4} = ( \frac{8}{10} \times \frac{3}{8} )^{4} = ( \frac{3}{10} ) ^{4} = \frac{81}{10000} [/tex]
c)
[tex](4 \frac{1}{2} ) ^{3} \times ( - \frac{2}{3} )^{3} = ( \frac{9}{2} \times - \frac{2}{3} ) ^{3} = ( - 3)^{3} = - 27[/tex]
d)
[tex](2 \frac{1}{2} ) ^{4} \times (0.6)^{4} \div ( - 15) ^{4} = ( \frac{5}{2} \times \frac{6}{10} \div - 15) ^{4} = ( \frac{3}{2} \div - 15) ^{4} = ( \frac{3}{2} \times - \frac{1}{15} ) ^{4} = ( - \frac{1}{10} ) ^{4} = \frac{1}{10000} [/tex]